Enhancing Descriptive Text Writing Through SQ5R Strategy and Audio-Visual Media: A Classroom Action Research - Masriyani Masriyani; Mohammad Tahir; Syamsuddin Syamsuddin (Journal of Innovation and Research in Primary Education, 2026)
This study aims to describe the application of the SQ5R strategy based on audio-visual media in learning to write descriptive texts in grade V of SDN Solonsa. The background of this study is the low ability of students to write descriptive texts in a coherent, interesting, and in accordance with good language rules. The research method used is classroom action research (CAR) which is carried out in two cycles, each consisting of planning, action implementation, observation, and reflection. The subjects of the study were 24 grade V students of SDN Solonsa. Data were collected through observation, interviews, writing tests, and documentation. The results showed that the application of the SQ5R strategy (Survey, Question, Read, Reflect, Recite, Review) based on audio-visual media can improve students' ability to write descriptive texts. In cycle I, the average writing score of students reached 72 with a learning completeness of 66.7%, while in cycle II it increased to an average of 86 with a learning completeness of 91.7%. Audio-visual media helps students understand objects concretely, while the SQ5R steps guide students to think systematically in the writing process. Thus, it can be concluded that the implementation of the SQ5R strategy based on audio-visual media is effective in improving the descriptive text writing skills of fifth-grade students at Solonsa Elementary School. This strategy can be recommended as an alternative for engaging and meaningful writing learning in elementary schools.